Credit constraints, idiosyncratic risks, and wealth distribution in a heterogeneous agent model - Christiane Clemens; Maik Heinemann (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2007)
This paper examines the effects of credit market imperfections and idiosyncratic risks on occupational choice, capital accumulation, as well as on the income and wealth distribution in a two sector heterogeneous agent general equilibrium model. Workers and firm owners are subject to idiosyncratic shocks. Entrepreneurship is the riskier occupation. Compared to an economy with perfect capital markets, we find for the case of serially correlated shocks that more individuals choose the entrepreneurial profession in the presence of credit constraints, and that the fluctuation between occupations increases too. Workers and entrepreneurs with high individual productivity tend to remain in their present occupation, whereas low productivity individuals are more likely to switch between professions. Interestingly, these results reverse if we assume iid shocks, thus indicating that the nature of the underlying shocks plays an important role for the general equilibrium effects. In general, the likelihood of entrepreneurship increases with individual wealth.
Keywords: C68; D3; D8; D9; G0; J24; 330; DSGE model; wealth distribution; occupational choice; credit constraints; Berufswahl; Unternehmer; Arbeitskräfte; Dynamisches Gleichgewicht; Schock; Kreditmarkt; Unvollkommener Markt; Investition; Vermögensverteilung; Verschuldungsrestriktion; Theorie